Use of molecular epidemiology to monitor the nosocomial dissemination of methicillin-resistant Staphylococcus aureus in a University Hospital from 1991 to 2001 - Beretta,A.L.R.Z. (2004)
Methicillin-resistant Staphylococcus aureus (MRSA) has been the cause of major outbreaks and epidemics among hospitalized patients, with high mortality and morbidity rates. We studied the genomic diversity of MRSA strains isolated from patients with nosocomial infection in a University Hospital from 1991 to 2001. The study consisted of two periods: period I, from 1991 to 1993 and period II from 1995 to 2001. DNA was typed by pulsed-field gel electrophoresis and the similarity among the MRSA strains was determined by cluster analysis. During period I, 73 strains presented five distinctive DNA profiles: A, B, C, D, and E. Profile A was the most frequent DNA pattern and was identified in 55 (75.3%) strains; three closely related and four possibly related profiles were also identified. During period II, 80 (68.8%) of 117 strains showed the same endemic profile A identified during period I, 18 (13.7%) closely related profiles and 18 (13.7%) possibly related profiles and, only one strain presented an unrelated profile. Cluster analysis showed a 96% coefficient of similarity between profile A from period I and profile A from period II, which were considered to be from the same clone. The molecular monitoring of MRSA strains permitted the determination of the clonal dissemination and the maintenance of a dominant endemic strain during a 10-year period and the presence of closely and possibly related patterns for endemic profile A. However, further studies are necessary to improve the understanding of the dissemination of the endemic profile in this hospital.